Fabrication of Al-based Metallic Glasses by Mechanical Alloying and Hot Consolidation - Ng, Chun Ming (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
This project is related to fabrication of aluminium based amorphous metallic glasses. Elemental powder of aluminium, copper and nickel were used for the purpose mentioned. The elemental powders with nominal composition (wt.%) of Al67Cu33-xNix, where x = 3, 5 and 10 were mechanical alloyed and characterized by using scanning electron microscope (SEM) and X-ray diffraction (XRD). The final results showed that milling of Al67Cu33-xNix powder for eight hours did not lead to the formation of amorphous powder.